2016
DOI: 10.1177/1687814016644578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gas quantity on two-phase flow characteristics of a mixed-flow pump

Abstract: The inlet gas quantity has a great influence on the performance and inner flow characteristics of a mixed-flow pump. In this article, both numerical and experimental methods are used to carry out this research work. The effects under the steady gas volume fraction state and the transient gas quantity variation process on the mixed-flow pump are investigated and compared in detail. It could be concluded that the head of the mixed-flow pump shows slight decline at the low gas volume fraction state, while it decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As a citation in some previous studies, these oscillations of bubbles can have a profound effect on the pressure fluctuations during pump operation. 39,40 From their results, the amplitude and magnitude of pressure fluctuations are sensitively affected by changes of the bubbles. The unsteady condition such as broad-band pressure fluctuation is proportional to the degree of cavitation and vapor volume fraction.…”
Section: Full-passage Analysismentioning
confidence: 99%
“…As a citation in some previous studies, these oscillations of bubbles can have a profound effect on the pressure fluctuations during pump operation. 39,40 From their results, the amplitude and magnitude of pressure fluctuations are sensitively affected by changes of the bubbles. The unsteady condition such as broad-band pressure fluctuation is proportional to the degree of cavitation and vapor volume fraction.…”
Section: Full-passage Analysismentioning
confidence: 99%
“…However, where the inlet pressure is further reduced, the pressure fluctuation at r ¼ 0.41 is less than that of r ¼ 0.78, whereas the amount of the generated vapor for type B was larger at r ¼ 0.41 than r ¼ 0.78 as shown in Figures 9(d) and (e) and 14. The previous studies 58,59 had confirmed that the amount of vapor increases as the inlet pressure decreases, and the pressure fluctuation occurs gradually with the generated vapor considerably in the cavitation state. Based on the above results of this study, the correlation between the stability of internal flow and pressure fluctuation with the development of vapor seems to be somewhat reasonable, but it is further confirmed that the correlation is not perfectly proportional especially in severe cavitation state.…”
Section: Pressure Fluctuationmentioning
confidence: 82%
“…With technology advancements, the two-phase centrifugal pump studies began to include computer simulations using finite element methods. Fu et al [19] presented a 3D model of a centrifugal pump in 2016. The elements of a centrifugal pump assembly were modeled in a drafting software and was imported into a finite element method (FEM) program.…”
Section: Introductionmentioning
confidence: 99%